2011
DOI: 10.1002/hbm.21171
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation of the α2b‐adrenoceptor affects neural correlates of successful emotional memory formation

Abstract: Our results demonstrate that the ADRA2B polymorphism influences emotional memory formation but not memory retrieval in the amygdala and left inferior frontal gyrus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 39 publications
(46 reference statements)
2
8
0
Order By: Relevance
“…Findings of sustained amygdala activity in depressed populations (Siegle et al, 2007;van Wingen et al, 2010) indicate that similar effects could counteract or overshadow any amygdala involvement in moodcongruent stimulus detection. Moreover, our data are in line with studies using stress-induction in healthy controls (van Marle et al, 2009), where there is a shift of amygdala function towards heightened sensitivity with lower levels of emotional specificity following an experimental stress-induction procedure, a pattern of results suggestive for a state of indiscriminate hyper-vigilance. The idea of amygdala hyperactivity during an acute mood-state that will put more brain systems on alert is very well in line with recent theories of depression (Whalen et al, 2002).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Findings of sustained amygdala activity in depressed populations (Siegle et al, 2007;van Wingen et al, 2010) indicate that similar effects could counteract or overshadow any amygdala involvement in moodcongruent stimulus detection. Moreover, our data are in line with studies using stress-induction in healthy controls (van Marle et al, 2009), where there is a shift of amygdala function towards heightened sensitivity with lower levels of emotional specificity following an experimental stress-induction procedure, a pattern of results suggestive for a state of indiscriminate hyper-vigilance. The idea of amygdala hyperactivity during an acute mood-state that will put more brain systems on alert is very well in line with recent theories of depression (Whalen et al, 2002).…”
Section: Discussionsupporting
confidence: 90%
“…The idea of amygdala hyperactivity during an acute mood-state that will put more brain systems on alert is very well in line with recent theories of depression (Whalen et al, 2002). Our findings together with those of van Marle et al (2009) add to that by showing that a mood-induced indiscriminate hyper-vigilance of amygdala seems to have a general adaptive value that also applies to the general population.…”
Section: Discussionsupporting
confidence: 90%
“…These results suggest that this polymorphism did not affect these processes. Moreover, a recent study showed that the modulations by + 901 Ins/Del of the neural correlations of emotional memory mainly emerge in the formation phase (Urner et al, 2011). However, the polymorphism did not significantly affect arousal for encoding emotion valence (Naudts et al, 2012) or for arousal ratings of emotional versus neutral photographs (De Quervain et al, 2007).…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, variants of the ADRB2B gene have been associated with activations in these brain regions, particularly the right inferior frontal gyrus, the insula, and the basal ganglia system. For example, the + 901 Del/Ins variant of the ADRA2B gene modulates the neural activity of the amygdala/insula/inferior frontal gyrus (de Quervain et al, 2007;Rasch et al, 2009;Cousijn et al, 2010;Urner et al, 2011).…”
Section: Discussionmentioning
confidence: 99%